Open Access Perceptions, Strategies, and Digital Literacies: A Case Study of a Scholarly-Led Journal - Noella Edelmann; Judith Schoßböck (Publications, 2020)
Open access (OA) publications play an important role for academia, policy-makers, and practitioners. Universities and research institutions set up OA policies and provide authors different types of support for engaging in OA activities. This paper presents a case study on OA publishing in a scholarly community, drawing on qualitative and quantitative data gained from workshops and a survey. As the authors are the managing editors of the OA eJournal for eDemocracy and Open Government (JeDEM), the aim was to collect data and insights on the publication choices of authors interested in OA publishing and other crucial factors such as personal attitudes to publishing, institutional context, and digital literacy in order to improve the journal. In the first phase, two workshops with different stakeholders were held at the Conference for e-Democracy and Open Government (CeDEM) held in Austria and in South Korea in 2016. In the second phase, an online survey was sent to all the users of the e-journal JeDEM in October 2019. From the workshops, key differences regarding OA perception and strategies between the stakeholder groups were derived. Participants strongly perceived OA publishing as a highly individualist matter embedded within a publishing culture emphasizing reputation and rankings. The survey results, however, showed that institutional support differs considerably for authors. Factors such as visibility, reputation, and impact play the biggest role for the motivation to publish OA. The results from both inquiries provide a better understanding of OA publishing attitudes and the relevant digital literacies but also suggest the need to investigate further the enablers or difficulties of scholarship, particularly in a digital context. They clearly point to the potential of regularly addressing the users of the journal as well as communicating with them the more nuanced aspects of OA publishing, non-traditional metrics, or respective digital literacies, in order to reduce misconceptions about OA and to support critical stances.